Self-Efficacy in Speaking Based Activities for Art and Design Students - Amirullah Abduh; Karta Jayadi; Anshari Anshari; Muhammad Basri; Muhammad Arham (International Journal of Language Education, 2022)
This research paper aims to explore a potential model for speaking through which consists of: a) strategies of using art as a medium for learning English; b) challenges to use art as a medium for learning English. This qualitative case study uses semi-structured interviews and observation in three schools of South Sulawesi. Data were analyzed through thematic analysis approach. The findings show that there were four strategies of using art as a medium for learning English, namely: a) using art to learn vocabulary; b) using art to learn grammar; c) employing art as a medium for learning process simple writing and; d) using art as a medium for speaking. In addition, the challenges they face include linguistic and practical challenges. The findings of this study extend the debates of learning English through art media. The implication of this study is that using art as a medium for learning English can be a model for EFL in similar contexts.